2016
DOI: 10.1177/1757975915569514
|View full text |Cite
|
Sign up to set email alerts
|

Grassroots volunteers in context: rewarding and adverse experiences of local women working on HIV and AIDS in Kilimanjaro, Tanzania

Abstract: Many nongovernmental organizations in Africa rely on grassroots volunteers to provide critical health services. Considering context and the interplay of individual, organizational, and societal influences on the experience of volunteers, this paper addresses three questions: What do grassroots volunteers contribute? What organizational processes promote volunteer engagement? What are the positive and negative consequences of volunteering? Eighteen members and staff of the Tanzanian HIV and AIDS NGO, KIWAKKUKI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This model provides an analytical frame for examining collaborative working arrangements ( Endresen, 2007 ; Dosbayeva, 2010 ; Corbin et al , 2012 , 2013 ; Corwin et al , 2012 ). Researchers have chosen to use the BMCF as a guide for practice ( Haugstad, 2011 ; Corbin et al , 2012 ) and as an evaluation tool ( Amaral-Sabadini et al , 2012 ; Corbin et al , 2015 ) for health promotion partnerships because of its focus on the processes of partnership and its acknowledgement of both negative and positive interactions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This model provides an analytical frame for examining collaborative working arrangements ( Endresen, 2007 ; Dosbayeva, 2010 ; Corbin et al , 2012 , 2013 ; Corwin et al , 2012 ). Researchers have chosen to use the BMCF as a guide for practice ( Haugstad, 2011 ; Corbin et al , 2012 ) and as an evaluation tool ( Amaral-Sabadini et al , 2012 ; Corbin et al , 2015 ) for health promotion partnerships because of its focus on the processes of partnership and its acknowledgement of both negative and positive interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that having substantial partner resources (>6000 grassroots members) balanced the financial contributions of Northern partners and empowered the Southern organization. Multiple funding streams also strengthen the Southern organization’s position as a partner, as did a clear focus on the locally developed organizational mission Input interaction (distrust), input interaction (power), antagony feedback Latinos in a Network for Cancer Control (LINCC), USA ( Corbin et al , 2015 ) A qualitative evaluation of a community-academic partnership working to reduce cancer-related health disparities. The analysis employed the Bergen Model of Collaborative Functioning as the analytic frame to analyze 19 interviews with diverse community and academic partners.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations